2018
DOI: 10.3233/jad-170881
|View full text |Cite
|
Sign up to set email alerts
|

Connected Speech Features from Picture Description in Alzheimer’s Disease: A Systematic Review

Abstract: The language changes that occur over the course of Alzheimer's disease (AD) can impact communication abilities and have profound functional consequences. Picture description tasks can be used to approximate everyday communication abilities of AD patients. As various methods and variables have been studied over the years, current knowledge about the most affected features of AD discourse in the context of picture descriptions is difficult to summarize. This systematic review aims to provide researchers with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 111 publications
3
88
2
1
Order By: Relevance
“…Overall, individuals with MCI produce speech which is slower than the speech of HC individuals. Earlier studies suggest that MCI individuals produce longer pauses and longer segmental duration (see also Slegers et al 2018). Our finding may suggest that longer vowel duration and longer pause duration can be attributed to the overall slower speech.…”
Section: Discussionsupporting
confidence: 55%
“…Overall, individuals with MCI produce speech which is slower than the speech of HC individuals. Earlier studies suggest that MCI individuals produce longer pauses and longer segmental duration (see also Slegers et al 2018). Our finding may suggest that longer vowel duration and longer pause duration can be attributed to the overall slower speech.…”
Section: Discussionsupporting
confidence: 55%
“…That is, our findings may also suggest further utilization of executive functioning skills, specifically strategic search (Birn et al, 2010;Li et al, 2017), by individuals with dementia, to find and retrieve the target verbs relative to cognitively healthy older adults. People with dementia not only lose control of attentional and executive functioning skills as their dementing disease progresses, but also demonstrate significant semantic degradation and impaired access to semantic representations (Reilly et al, 2011;Stopford et al, 2012;Szatloczki et al, 2015;Belleville et al, 2017;Slegers et al, 2018). The upregulation of frontal lobe areas may indicate additional burden to support attention and executive functions (i.e., search strategies) and organization of semantic clusters to keep up their verb fluency performance in the midst of a loss of semantic information.…”
Section: Brain Activation Differences Between Cognitively Healthy Oldmentioning
confidence: 99%
“…There are also potential difficulties with manually coding the part of speech (POS) categories of every token, so previous studies on the POS analysis have rarely examined every word of an utterance. This is a problem in studying language use of patients with dementia, because many previous studies have shown that patients with dementia tend to produce fewer words than controls (e.g., Ash et al 2013;Slegers et al, 2018;Tappen et al, 2002), but failed to show in detail which POS categories were reduced in which patient groups due to the efforts required for manual POS tagging. Because of the effort involved, large-scale studies are rarely performed.…”
Section: Introductionmentioning
confidence: 99%